Remote consultations in general practice - A systematic review - Vodička Staša; Zelko Erika (Sciendo, 2022)
Remote consultations in general practice can be very useful form of telemedicine, which is basically a way to exchange medical information to improve the clinical health of patients when the patient and their general practitioner (GP) are not on the same place at the same time. This concept was developed in the 1980s to provide health care to patients who lived in remote areas.